Trading for SDGs: Trade Liberalization and Human Development in the Emerging Economies - Islam, Mohammad Monirul; Fatema, Farha (Asian Development Policy Review, 2017)
This study examines the effect of trade liberalization on human development which is the core focus of sustainable development goals (SDGs). It uses trade openness as proxy to trade liberalization and human development index (HDI) as well as its three sub-indexes namely education, health, and income as indicators of human development. The study focuses on emerging economies as the research sample considering their significance in the world trade and deals with a panel data set of 43 emerging countries for the period of 1995-2014. Due to cross-sectional dependence in the data set Driscoll-Kraay estimator has been applied to the regression models. The effect of trade openness on HDI and its three sub-indexes is identified for all the emerging economies and their three subgroups such as EAGLE, NEST and other emerging countries separately for the robustness of the analysis. The results of the study suggest that higher trade openness significantly progresses human development status in the emerging economies in all aspects. Both human capital accumulation and per capita GDP have a positive impact on human development whereas the effect of GDP growth is negative. The religious and cultural factors show a mixed effect on human development in the emerging economies.